Perceived Physical Progress and Mental Improvement Among Midlife Women Practicing the 3D Movement Method: A Brief Report from a Cross-Sectional Survey - Manaenkova, Zarina; A. Santanna, Ekaterina (Journal of Sports and Exercise Medicine, 2025)
Background Mind–body exercises are frequently used to support well-being during the menopausal transition, but perceived physical and psychological outcomes associated with practices such as the 3D Movement Method have not been quantitatively assessed. Objective To examine associations between characteristics of the 3D Movement Method and women’s self-reported physical and mental improvement during the menopausal transition. Methods Cross-sectional survey data from 330 women aged ≥ 35 years were analyzed using general linear models. Perceived physical progress and mental improvement were each assessed using single-item, 15-point scales. Independent variables included practice frequency, duration of experience, explanation clarity, satisfaction, baseline health status (SF-36 Physical and Mental Component Summary scores), age, and menopausal status. Results The model for physical progress was significant, F(16, 144) = 6.26, p < .001, R² = .41. Greater practice frequency, longer experience, clearer instructional explanations, and higher satisfaction were each independently associated with higher perceived physical progress. The mental improvement model was also significant, F(16, 96) = 2.25, p = .008, R² = .27, identifying satisfaction as the sole significant predictor. Baseline health, age, and menopausal status did not predict outcomes in either model. Conclusions Perceived physical progress was shaped by structured engagement parameters consistent with deliberate-practice principles, whereas perceived mental improvement was primarily linked to subjective satisfaction, a pattern compatible with motivational accounts of engagement. The 3D Movement Method may support women’s health across the menopausal transition when designed to optimize clarity, engagement, and experiential quality.
Keywords: menopausal transition; 3D Movement Method; perceived progress; deliberate practice; women’s health; mind–body practice